2013
DOI: 10.1136/archdischild-2013-305145
|View full text |Cite
|
Sign up to set email alerts
|

Headache after lumbar puncture: randomised crossover trial of 22-gauge versus 25-gauge needles

Abstract: There was little difference in the occurrence of post-LP headache or any headache between procedures carried out using the 22-gauge or 25-gauge needles. Depending on the circumstances of the procedure and the experience of the operator, either gauge may be appropriate for an LP in a child.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 20 publications
(14 reference statements)
2
14
0
Order By: Relevance
“…Twenty‐eight studies, published between 1970 and 2016 (references in this paragraph resulted from the systematic literature review, Table 3), compared the performance and complications of different diameters of needles. No differences were detected in six studies comparing different needle diameters [47–52], whereas one study concluded that needles with a larger diameter (≤22G) had a positive effect on collection time and resulted in less failures [53]. The LP feasibility study performed in memory clinic settings did not show that large‐bore diameter needles confer independent risk compared with small bore needle types.…”
Section: Resultsmentioning
confidence: 97%
“…Twenty‐eight studies, published between 1970 and 2016 (references in this paragraph resulted from the systematic literature review, Table 3), compared the performance and complications of different diameters of needles. No differences were detected in six studies comparing different needle diameters [47–52], whereas one study concluded that needles with a larger diameter (≤22G) had a positive effect on collection time and resulted in less failures [53]. The LP feasibility study performed in memory clinic settings did not show that large‐bore diameter needles confer independent risk compared with small bore needle types.…”
Section: Resultsmentioning
confidence: 97%
“…Using smaller gauge needles; this is supported by adult practice studies,9 although a recent paediatric study found little corroborating evidence 10…”
Section: Clinical Questionsmentioning
confidence: 98%
“…Preventive measures include: Using smaller gauge needles; this is supported by adult practice studies,9 although a recent paediatric study found little corroborating evidence 10

Orientating the needle bevel parallel to the spine rather than inserting perpendicularly (7.9% headache rate vs 19.3%) 11.

…”
Section: Clinical Questionsmentioning
confidence: 99%
“…Post-procedure bed rest has been suggested, but not found to be helpful (Lee et al 2007 ). Studies investigating the use of smaller gauge needles have not found significant differences in incidence (Ebinger et al 2004 ;Crock et al 2014 ). Use of an atraumatic, or "pencil-tip," needle (i.e., Whitacre), has been shown to signifi cantly reduce the incidence of post-LP headache although one study found no difference (Kokki et al 1999 ;Thomas et al 2000 ;Apiliogullari et al 2010 ).…”
Section: Post-lumbar Puncture Headachementioning
confidence: 96%
“…It is theorized that loss of CSF pressure leads to traction on painsensitive intracranial structures or an increase in cerebrovascular blood volume with resultant vasodilation, either of which could cause headache (Turnbull and Shepherd 2003 ). In children, the incidence of post-LP headache has been reported to be between 6 and 15 % and has been shown to occur in even young children although is much more common in adolescents (Kokki et al 1999 ;Lee et al 2007 ;Crock et al 2014 ).…”
Section: Post-lumbar Puncture Headachementioning
confidence: 97%